Advanced imaging of gas diffusion layers: A comparison between focused ion beam scanning electron microscopy and X-ray computed tomography - Hossein Pourrahmani; Thomas B. Ferriday; Raha Razmara; Hossein Madi; Jan Van herle (Materials Letters: X, 2025)
With the advances in clean technologies, the role of fuel cells and batteries is becoming increasingly vital. Proton exchange membrane fuel cells are known to be the best candidates for low-temperature and portable operations, such as hydrogen cars. The efficiency and longevity of these fuel cells can be feasible through detailed microstructural analysis. In this regard, advanced imaging techniques are being used to visualize the structure of the different layers of PEMFCs including the membrane, catalyst layer, and gas diffusion layer. This study’s focus and novelty is to compare the focused ion beam scanning electron microscopy and X-ray Computed Tomography scanning for the microstructural imaging of the GDL.